Style and creativity in design - Chan, Chiu-Shui (Studies in Applied Philosophy, Epistemology and Rational Ethics,, 2015)
This book looks at causative reasons behind creative acts and stylistic expressions. It explores how creativity is initiated by design cognition and explains relationships between style and creativity. The book establishes a new cognitive theory of style and creativity in design and provides designers with insights into their own cognitive processes and styles of thinking, supporting a better understanding of the qualities present in their own design.  An explanation of the nature of design cognition begins this work, with a look at how design knowledge is formulated, developed, structured and utilized, and how this utilization triggers style and creativity. The author goes on to review historical studies of style, considering a series of psychological experiments relating to the operational definition, degree, measurement, and creation of style. The work conceptually summarizes the recognition of individual style in products, as well as the creation of such styles as a process before reviewing studies on creativity from various disciplines, presenting case studies and reviewing works by master architects.   Readers will discover how creativity is initiated by design cognition. A summary of the correlations between creativity and style, expressed as a conceptual formula describing the cognitive phenomenon of style and creativity concludes the work. The ideas presented here are applicable to all design fields, allowing designers to comprehend and improve their design processes to produce creative, stylistically unique products.